Bond strength evaluation of palm oil fuel ash-based geopolymer normal weight and lightweight concretes with steel reinforcement - Mo, Kim Hung; Yeap, Kee Wei; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Bashar, Iftekhair Ibnul (Taylor & Francis, 2018)
This article presents a comparison of the bond behaviour between palm oil fuel ash (POFA)-derived geopolymer and conventional cement-based normal weight and lightweight concretes. A total of 16 variables were tested, which includes concrete cover (50 and 100 mm), bar diameter (12 and 16 mm) and types of concrete (POFA-based geopolymer normal/ lightweight concrete and cement-based normal/lightweight concrete). Results showed that the bond strength of cement-based concretes had higher critical bond stress and ultimate bond strength as well as lower slip at the ultimate bond strength compared to the corresponding POFA-based geopolymer concretes. The cement-based and geopolymer lightweight concrete specimens also exhibited greater bond strength than the normal weight concrete specimens. All of the concrete specimens generally exhibited similar bond stress-slip curves. Besides that, bond strength models proposed in the past predicted satisfactory match (difference of up to 35%) to the experimental ultimate bond strength values in the case of cement-based normal weight concrete and geopolymer concrete whereas a difference in the range of 16–138% was found for the case of lightweight concrete.